Annie (1981) [videorecording (Blu-Ray)] - Sobieski, Carol; Finney, Albert, 1936-2019; Burnett, Carol; Peters, Bernadette; Reinking, Ann; Curry, Tim; Holder, Geoffrey, 1930-2014; Herrmann, Edward, 1943-2014; Quinn, Aileen (Sony Pictures Home Entertainment, 2012)
The story of a plucky, red-haired girl who dreams of life outside her dreary orphanage. One day, Annie is chosen to stay for one week with the famous billionaire 'Daddy' Warbucks. One week turns into many and the only person standing in the way of Annie's fun is Miss Hannigan, the gin-soaked ruler of the orphanage. Will Miss Hannigan's zany attempts to kidnap the irrepressible Annie succeed? Enjoy all the unforgettable songs, including It's A Hard Knock Life and Tomorrow.